MASALAH GIZI PADA ANAK USIA SEKOLAH - Jinan Nabila Aulia (Jurnal Ilmiah Kesehatan Media Husada, 2022)
Nutrition is the essence of food that is beneficial to the health of the body. Nutrients are divided into two, namely macro and micro. Examples of macronutrients are carbohydrates, fats, and proteins. Meanwhile, micronutrients include vitamins, minerals, water and fiber. Data from UNICEF in 2018 states that about 3 out of 10 children less than 5 years old are stunted, 1 in 10 is underweight, and a fifth of them are overweight. Children at school age are still in the stage of growing and developing so they are quite at risk for nutritional problems. The writing of this article was obtained from various sources in the form of scientific journals and guidelines for related institutions. Source searches were carried out on various online portals such as Medscape, NCBI Google Scholar and other health websites with the keywords “Bad Nutrition in School Age Children”, “Malnutrition”, and “School Cjild Nutrition”. A child who has nutritional problems is susceptible to disease and there is a decline in academic achievement so the Ministry of Education and Culture created the School Children's Nutrition Program (Progas) in 2018, namely providing breakfast to students to improve nutritional status, breakfast habits, and character education.